SOSIALISASI PURIFASI UDARA DI DALAM RUANGAN MELALUI PEMANFAATAN MEDIA INDOOR PLANTS PADA MAHASISWA - Isnawati, Uzlifatul Masruroh (Batara Wisnu : Indonesian Journal of Community Services, 2021)
During the pandemic of Covid-19 outbreak, maintaining air quality in the house or room is very important considering that most activities are carried out indoors (indoor activities). Some of the activities carried out including e making air ventilation in each room, opening windows in the morning and letting sunlight enter the room so that there is an exchange or healthy air circulation in the room, and also by putting indoor plants which enable to purify air in the surrounded area. t. In this program, the author makes an activity by socializing the types of plants that are useful as air purification. Some activities were briefly explained and figured out for the students of Economics faculty Universitas Islam lamongan respectively